ANALISIS PENGARUH EKUITAS MEREK TERHADAP KEPUTUSAN PEMBELIAN PRODUK LAPTOP ACER - Fadlan Auliya; Miguna Astuti; Pusporini (2021)
This research belongs to the type of quantitative research with the aim of analyzing and proving the influence of the variables of brand awareness, brand association, perceived quality and brand loyalty partially and together on purchasing decisions for Acer laptop products. The population of this study are buyers or users of Acer laptop products in the DKI Jakarta province. With a sample of 100 respondents, using the Non-Probability Sampling method with the type of Purposive Sampling. Data was collected by distributing questionnaires. This study uses data analysis techniques with the Partial Least Square (PLS) method. The results showed that the brand awareness variable had a positive and significant effect on purchasing decisions, while other variables, namely brand associations, perceived quality, and brand loyalty had no effect on purchasing decisions.